Local polar order in the ferroelectic-relaxor Na₁/₂Bi₁/₂TiO₃ as studied by ²³Na NMR - Yablonskaya, Yu.E.; Aleksandrova, I.P.; Sukhovsky, A.A.; Ivanov, Yu.N. (Functional Materials, 2008)
²³Na NMR spectra have been measured in a very low magnetic field at temperatures between 293 K and 729 K. The achieved spectral resolution is sufficient to test various models of short-range order in the Na₁/₂Bi₁/₂TiO₃ structure using computer simulations of the spectral line shape. The best agreement between experimental and calculated spectra has been obtained for the inhomogeneous structure where the polar nanoscale areas with Na displaced along the pseudo-cubic directions [111]p coexist in the 293 K-580 K temperature region with the tetragonal phase insertions with Na displaced along [100]p and the "matrix" having very small deviations from the cubic structure.